Non-thermal atmospheric plasma synthesis of ammonia in a DBD reactor packed with various catalysts. (5th December 2019) - Xie, Qinglong; Zhuge, Shaoyuan; Song, Xiaofang; Lu, Meizhen; Yu, Fengwen; Ruan, Roger; Nie, Yong
Abstract: Plasma synthesis of ammonia (NH3 ) is a potential and sustainable pathway for nitrogen fixation. In this study, non-thermal plasma (NTP) synthesis of NH3 was conducted in a packed-bed dielectric barrier discharge (DBD) reactor. Different catalysts, including alumina (Al2 O3 ), light magnesium oxide (L-MgO), heavy magnesium oxide (H-MgO), Ru/Al2 O3 and Ru/L-MgO, were filled in the reactor and compared for NH3 production. Various characterization techniques were used to determine the specific surface area and pore size, surface morphology, and surface acidity of the catalysts. The effects of reaction conditions on NH3 production were examined. Results showed that the optimal N2 /H2 volume ratio was 2:1 since a greater quantity of N2 favored the generation of plasma-excited nitrogen species. The synthesized NH3 can be adsorbed by the acid sites on Al2 O3, which reduced the NH3 yield. Higher total gas flow rate improved the NH3 production over various catalysts, mainly due to the reduced external diffusion resistance. More plasma-excited nitrogen and hydrogen species for NH3 synthesis were formed at higher discharge power, yet the increasing rate of NH3 yield became slower when the discharge power was higher than 32 W. Additionally, the NH3 desorption from the catalyst was enhanced at higher temperature, which resulted in higher NH3 yield.